2021
DOI: 10.1021/acsabm.1c00621
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Engineering in Vinylene-Linked Covalent Organic Frameworks for Enhanced Photocatalytic Degradation of Organic Contaminants and Disinfection of Bacteria

Abstract: Photocatalysis is regarded as one of the most promising technologies to remove organic contaminants. At present, most of the covalent organic frameworks (COFs) used as photocatalysts are connected by imine or borate bonds, which have relatively low stability and relatively poor π-delocalization. Herein, we report, for the first time, vinylene-linked COFs constructed by various diacetylene and triazine moieties for photocatalytic degradation of organic contaminants and disinfection of bacteria. The pioneering i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Due to the high crystallinity, well-defined one-dimensional pore structures, structural diversity, and high stability, two-dimensional (2D) COFs have attracted tremendous attention and exhibit great potential application in many research fields including gas absorption and separation, electronic applications, , catalysis, water treatment, and energy storage. A recent investigation demonstrated that COFs could act as an effective sulfur host and provide highly ordered pores for sulfur impregnation, avoiding the volume expansion during the charge–discharge cycling . In addition, introduction of interaction sites for LiPSs on the pore surface can prevent LiPS from shuttling, leading to improvement of the electrochemical performance of LSBs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high crystallinity, well-defined one-dimensional pore structures, structural diversity, and high stability, two-dimensional (2D) COFs have attracted tremendous attention and exhibit great potential application in many research fields including gas absorption and separation, electronic applications, , catalysis, water treatment, and energy storage. A recent investigation demonstrated that COFs could act as an effective sulfur host and provide highly ordered pores for sulfur impregnation, avoiding the volume expansion during the charge–discharge cycling . In addition, introduction of interaction sites for LiPSs on the pore surface can prevent LiPS from shuttling, leading to improvement of the electrochemical performance of LSBs.…”
Section: Introductionmentioning
confidence: 99%
“…under light, causing the oxidation of bacterial membrane structures and killing bacteria. [852][853][854][855][856][857] Additionally, COFs can be composited with other antimicrobial nanomaterials, such as Fe-based MOFs, 858 MXenes, 859 and nanosilver, 860 to enhance the adhesion of the biomaterials on the bacterial surface and improve the antimicrobial activity. Fe-metalated COFs can induce bacterial death by virtue of the chemodynamic activity of Fe(II).…”
Section: Biomedicinementioning
confidence: 99%
“…To demonstrate the antimicrobial activity of the synthesized CONs against Gram-negative bacterium Escherichia coli ( E. coli ), 13 inactivation by light irradiation was evaluated. After 45 min of LED-light irradiation, a 10-fold reduction in the survival rate of E. coli treated with A-CONs was observed ( Fig.…”
mentioning
confidence: 99%
“…[10][11][12] Among polymeric materials, covalent organic frameworks (COFs) are promising photocatalysts for inactivating biological targets, and thus further material development is warranted for their practical application. [13][14][15] We have been studying COFs-derived organic nanomaterials such as nanodisks, and the effect of exfoliation on their photocatalytic activities in various processes, such as hydrogen production under anaerobic conditions. 16,17 As a result, we found that exfoliation occurs and photocatalytic activity is enhanced by simply stirring the material in water up to its boiling point for 20 h. 16 Recently, several groups have reported that exfoliation of imine-bound COFs is enhanced under acidic conditions such as pH 1 in organic solvents.…”
mentioning
confidence: 99%
See 1 more Smart Citation